A Civic Spirituality of Sanctification: John Calvin. Edited by Roger Haight, SJ, Alfred Pach III, and Amanda Avila Kaminski - Balserak, Jon (The journal of theological studies, 2025)
This series exists for the academic community of teachers and learners. It has published 11 volumes to date. Along with portions from a ‘classic’ text, the